1968
DOI: 10.1121/1.1910870
|View full text |Cite
|
Sign up to set email alerts
|

Stress Sensitivity of Piezoelectric Ceramics: Part 3. Sensitivity to Compressive Stress Perpendicular to the Polar Axis

Abstract: Measurements are reported of the change in permittivity, loss, and the piezoelectric constants, d 31 and d 32 for piezoelectric ceramic transducer materials subjected to high stress perpendicular to the polar axis (T1). Ceramics useful fur high-power applications PTZ-4 and PTZ-8 and some donor-doped ceramics of high .sensitivity hut with high losses that make such applications unwise (PZT-5A and PZT-5H) were tested. Permittivity generally. decreased with stress, T 1 opposite to results with parallel stress, T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(41 citation statements)
references
References 0 publications
3
37
0
1
Order By: Relevance
“…In the case where large fields or stress are applied the theory cannot account for the behavior of piezoelectric materials and non-linear effects have been reported by a variety of authors. Berlincourt and Krueger [1959] looked at the general aspects of non-linearity as a function of stress and field while Krueger [1968] and others studied the stress dependence of the material properties of piezoelectric ceramics. Recent work by Vinogradov [1999] investigated the mechanical and viscoelastic properties of PVDF as a function of stress, time and temperature.…”
Section: Quasi-static Measurementsmentioning
confidence: 99%
“…In the case where large fields or stress are applied the theory cannot account for the behavior of piezoelectric materials and non-linear effects have been reported by a variety of authors. Berlincourt and Krueger [1959] looked at the general aspects of non-linearity as a function of stress and field while Krueger [1968] and others studied the stress dependence of the material properties of piezoelectric ceramics. Recent work by Vinogradov [1999] investigated the mechanical and viscoelastic properties of PVDF as a function of stress, time and temperature.…”
Section: Quasi-static Measurementsmentioning
confidence: 99%
“…Material properties were found to vary with the electro-mechanical boundary conditions, as well as time-history. The dependence of dielectric permittivity on the applied stress and electric field was also observed (Krueger, 1967(Krueger, , 1968Brennan and McGowan, 1997;Jordan et al, 2000). Experiments on doped PZT ceramics were pursued to determine the polarization domain switching under high electric fields and compressive stresses in order to explain the nonlinear effects (Lynch, 1996, Zhang et al, 1997Fan et al, 1999;Ching-Yu and Hagood, 2000;Lin and Hagood, 2000;Yang et al, 2000).…”
Section: State Of the Art In Active Materials Actuators Modeling And Cmentioning
confidence: 99%
“…Kruegar [3,4] studied the stress sensitivity of piezoelectric ceramics to compressive stress parallel and perpendicular to the poling direction, respectively, and found that the former loading causes domain switch while the latter stabilizes the polarization. Huang et al [5] observed the non-linear behaviour of PLZT (lead lanthanum zirconate titanate) under electrical and mechanical loading.…”
Section: Introductionmentioning
confidence: 99%